Direct extraction of Eucommia ulmoides rubber by high-power ultrasound and optimization with response surface methodology. Issue 3 (3rd July 2022) - Wang, Donghui; Chen, Shang; Li, Youji; Han, Zhangying; Dai, Yahao; Huang, Yanrong
ABSTRACT: Using deseeding nutshell of Eucommia ulmoides as raw material, Eucommia ulmoides rubber (EUR) was directly extracted by high-power ultrasound with high efficiency and the extracting process was accomplished within half an hour at a relatively low temperature. The extract was identified as EUR ( trans -polyisoprene) by FT-IR and 1 H NMR. The effects of extraction solvents, liquid-to-material ratio, ultrasonic temperature, time, and power on the extraction yields of EUR were investigated, as well as their molecular weights. The procedure parameters were also optimized by the response surface method. The results show that petroleum ether is the most suitable solvent. The highest yield of EUR can reach 89.13% under the following optimized parameters: liquid-to-material ratio 10 (mL/g), ultrasonic power 243 W, ultrasonic time 23 min, and ultrasonic temperature 47°C. The ultrasonic extraction under investigated ultrasonic power shows no significant impact on its molecular weight, except for an extremely long time at high ultrasonic power. GRAPHICAL ABSTRACT: UF0001